Integrated final project / Mahadi Hamdan ... [et al.] - Hamdan, Mahadi; Mohd Mukthar, Mohd Fahril; Shamsudin, Masidaayu; Abd Rahman, Faradibah; Razuan, Rohainiza; Radzi, Erney (2001)
Cities developed over time due to both conscious an unconscious actus of men. Despite of the vasts scale and complexity of urban design, cities, can be designed and their growth shaped and directed